Influences of Cry1Ac Broccoli on Larval Survival and Oviposition of Diamondback Moth. Issue 1 (5th April 2015) - Yi, Dengxia; Cui, Shusong; Yang, Limei; Fang, Zhiyuan; Liu, Yumei; Zhuang, Mu; Zhang, Yangyong
Abstract : Larval survival and oviposition behavior of three genotypes of diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae), (homozygous Cry1Ac-susceptibile, Cry1Ac-resistant, and their F1 hybrids), on transgenic Bacillus thuringiensis (Bt) broccoli expressing different levels of Cry1Ac protein were evaluated in laboratory. These Bt broccoli lines were designated as relative low, medium, and high, respectively, according to the Cry1Ac content. Untransformed brocccoli plants were used as control. Larval survival of diamondback moth on non-Bt leaves was not significantly different among the three genotypes. The Cry1Ac-resistant larvae could survive on the low level of Bt broccoli plants, while Cry1Ac-susceptible and F1 larvae could not survive on them. The three genotypes of P. xylostella larvae could not survive on medium and high levels of Bt broccoli. In oviposition choice tests, there was no significant difference in the number of eggs laid by the three P. xylostella genotypes among different Bt broccoli plants. The development of Cry1Ac-susceptible and Cry1Ac-resistant P. xylostella on intact Bt plants was also tested in greenhouse. All susceptible P. xylostella larvae died on all Bt plants, while resistant larvae could survive on broccoli, which expresses low Cry1Ac protein under greenhouse conditions. The results of the greenhouse trials were similar to that of laboratory tests. This study indicated that high dose of Bt toxins in broccoli cultivars or germplasm lines is required for effective resistance management.